Use of Videoscribe Animation-Based Science E-Modules on Learning Retention of Junior High School - Khamsiah Mawar Fatmah; Sri Arwini Bahrun; Insih Wilujeng; Suyanta Suyanta; Sri Rejeki (Postgraduate, University of Mataram, 2023)
Learning retention is the ability of students to remember learning material after some time. The use of videoscribe animation-based science e-modules that can increase learning retention is rarely developed. The research aims to determine students' learning retention after using the videoscribe animation-based science E-module. This research is quantitative descriptive. The sample selection using cluster random sampling selected students from class VII.B of SMPN 5 Depok, Yogyakarta with a total of 32 students. The data collection technique is a test technique using a pretest and posttest question instrument totaling 6 questions. The test instrument is in the form of multiple-choice questions, to determine student retention, a retest is carried out one week after the posttest activity. The data analysis technique is quantitative descriptive to determine the score presentation. The pretest score percentage was 43.31% in the fair category, the posttest was 79.17% in the good category, and the retest score was 91.14% in the very good category. The use of videoscribe animation-based science e-modules influences student learning retention with the average being in the good category, indicating that student retention has increased after being taught using videoscribe animation-based e-modules